Pengaruh price earning ratio, debt equity ratio, dan return on equity terhadap harga saham syariah periode 2017-2019 - Amelia Oktrivina; Basis Gumilarsih Andamari; Firza Erwandi (LPMP Imperium, 2022)
This study aims to determine whether Price Earning Ratio (PER), Debt Equity Ratio (DER), and Return on Equity (ROE) partially affect stock prices. The data used in this study is secondary data taken from the official website of the Indonesia Stock Exchange. The sample in this study was 15 companies listed on the Indonesia Stock Exchange (IDX) at sharia index Jakarta Islamic Index (JII) for three years, namely in 2017-2019. The data analysis technique used is panel data regression using EViews 9. The results of this study indicate that PER, DER, and ROE partially affect stock prices.